Diversity and Versatility of Phagocytosis: Roles in Innate Immunity, Tissue Remodeling, and Homeostasis - Lim, Justin J.; Grinstein, Sergio; Roth, Ziv (Frontiers in Cellular and Infection Microbiology, 2017)
Phagocytosis, a critical early event in the microbicidal response of neutrophils, is now appreciated to serve multiple functions in a variety of cell types. Professional phagocytes play a central role in innate immunity by eliminating pathogenic bacteria, fungi and malignant cells, and contribute to adaptive immunity by presenting antigens to lymphocytes. In addition, phagocytes play a part in tissue remodelling and maintain overall homeostasis by disposing of apoptotic cells, a task shared by non-professional phagocytes, often of epithelial origin. This functional versatility is supported by a vast array of receptors capable of recognizing a striking variety of foreign and endogenous ligands. Here we present an abbreviated overview of the different types of phagocytes, their varied modes of signaling and particle engulfment, and the multiple physiological roles of phagocytosis.